Molecular mechanisms of skeletal muscle fibrosis and potential targeted therapeutic strategies - Gong, Jiahuan; Xu, Jingxuan; Zhang, Jitai; Shen, Yuntian; Sun, Hualin; Chen, Bingqian (Frontiers in Immunology, 2026)
Skeletal muscle fibrosis is a pathological process characterized by excessive deposition of extracellular matrix (ECM). It commonly occurs in various diseases such as muscular dystrophy, aging, cancer cachexia, and muscle injury. This condition leads to destruction of muscle structure, loss of function, and impaired regeneration, significantly affecting patients’ quality of life. This review systematically summarizes the molecular mechanisms underlying skeletal muscle fibrosis. Key signaling pathways include transforming growth factor-beta (TGF-β)/Smad, yes-associated protein/transcriptional coactivator with PDZ-binding motif (YAP/TAZ), inflammation and immune regulation, oxidative stress, and microRNA-mediated regulation. The roles of fibro/adipogenic progenitors (FAPs), macrophages, and myofibroblasts in this process are also discussed. Among these, the TGF-β/Smad pathway acts as a central driver of fibrosis by promoting the differentiation of FAPs into myofibroblasts and stimulating ECM synthesis. YAP/TAZ integrates mechanical and biochemical signals, further amplifying the fibrotic response. Inflammation, oxidative stress, and epigenetic regulators such as miRNAs and lncRNAs also contribute through complex networks. Regarding therapeutic strategies, this article highlights various interventions including pharmacological inhibition (e.g., TGF-β inhibitors, angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers (ACEIs/ARBs), antioxidants), gene- and RNA-targeting therapies (e.g., miRNA mimics or inhibitors), cell-based therapies (e.g., Mesenchymal Stem Cells (MSCs)), biological agents (e.g., anti-connective tissue growth factor (CTGF) antibodies), as well as physical and nutritional interventions (e.g., electroacupuncture, magnetic stimulation, natural compounds). These approaches demonstrate strong anti-fibrotic potential by modulating ECM metabolism, the immune microenvironment, and cellular behaviors. However, current research still faces challenges such as disease heterogeneity, optimal treatment timing, drug delivery issues, and long-term safety concerns. Therefore, future studies should focus on developing highly specific targeted therapies, integrating multi-omics technologies and imaging assessments, and advancing personalized combination strategies to ultimately achieve effective prevention and treatment of skeletal muscle fibrosis.